STUDENT’S MATHEMATICAL VALUE IN MATHEMATICS LEARNING USING NON-ROUTINE PROBLEM - Nurul Ain Safura; Nyimas Aisyah; Cecil Hiltrimartin; Indaryanti Indaryanti (Jurnal Cakrawala Pendidikan, 2018)
Abstract: This study aims to determine the ability of students in solving non-routine problems in learning mathematics in high school. The focus of the study is the ability of students in solving non-routine problems that include the value of objectism, value of control, value of mystery, value of progress, value of rationalism, and value of openness. The subject of this study was determined purposively, that was based on the diversity of answers. The selected subject was six students of class X SMA in Palembang. The data were collected using observation, test, and interview which were then analyzed descriptively. The results show that in general the ability of students in solving non-routine problems is dominated by the value of objectism, control, rationalism, and progress. The other two values which did not dominantly appear were mystery and openness. Keywords: mathematical value, non-routine problemNILAI MATEMATIKA (MATHEMATICAL VALUE) SISWA PADA PEMBELAJARAN MATEMATIKA MENGGUNAKAN SOAL NON RUTIN Abstrak: Penelitian ini bertujuan untuk mengetahui kemampuan siswa dalam menyelesaikan soal non rutin pada pembelajaran matematika di SMA. Fokus penelitian adalah kemampuan siswa dalam menyelesaikan soal non rutin yang meliputi nilai objektisme, nilai kontrol, nilai misteri, nilai kemajuan, nilai rasionalisme, dan nilai keterbukaan. Adapun subjek penelitian ini dipilih secara purposive, berdasarkan keberagaman jawaban. Subjek yang terpilih adalah enam orang siswa kelas X SMA di Palembang. Data dikumpulkan menggunakan observasi, tes, dan juga wawancara, yang kemudian di analisis secara deskriptif.  Hasil penelitian menunjukkan bahwa secara umum kemampuan siswa dalam menyelesaikan soal non rutin masih didominasi pada nilai objektisme, nilai kontrol, nilai rasionalisme, dan nilai kemajuan. Dua nilai lain yang tidak dominan muncul adalah nilai misteri dan nilai keterbukaan.Kata Kunci: nilai matematika, soal non rutin